Nano-metal modified biomass carbon adsorbent as well as preparation method and application thereof

Through the nanometal in-situ modification method, the problem of not obvious improvement in porous carbon regeneration performance in the existing technology is solved, and the high regeneration performance and initial adsorption capacity of nanometal modified biomass carbon adsorbents are achieved, reducing production costs and Environmental hazards.

CN119425620APending Publication Date: 2025-02-14GUANGDONG UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411547396.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing post-modification method for transforming metal-modified porous carbon has the problem of the hole being blocked, resulting in less significant improvement in regeneration performance.

Method used

Using nanometal in situ modification method, by making carbon source, transition metal salt, cellulose and solvent into colloidal dispersion, hydrothermal carbonization and heat treatment, a stable network interwoven structure is formed to avoid metal element or metal oxides. Block the hole.

Benefits of technology

The regeneration performance and initial adsorption capacity of nano-metal modified biomass carbon adsorbents are improved, and the high adsorption capacity is maintained after multiple recycles is used, and equipment costs and environmental hazards are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119425620A_ABST
    Figure CN119425620A_ABST
Patent Text Reader

Abstract

The invention relates to a nano-metal modified biomass carbon adsorbent as well as a preparation method and application thereof. The preparation method is a nano-metal in-situ modification method, pore channels of the obtained nano-metal modified biomass carbon adsorbent cannot be blocked by metal simple substances or metal oxides, and the stability of a network interlaced structure is high, so that the nano-metal modified biomass carbon adsorbent is high in adsorption capacity retention rate after being recycled for multiple times, and the adsorption capacity retention rate of the nano-metal modified biomass carbon adsorbent is high. The regeneration performance is good. In addition, the initial adsorption capacity of the nano-metal modified biomass carbon adsorbent obtained by the preparation method is higher than that of a carbon adsorbent obtained by a post-modification method. In addition, the preparation method is simple and easy to implement, and the equipment cost is reduced; meanwhile, toxic and harmful organic solvents or secondary high-temperature activation and hole expansion are not needed in the preparation process, so that the production cost is reduced, and the harm to the environment is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of air purification, and more specifically, to a nano-metal modified biomass carbon adsorbent and a preparation method and application thereof. Background Art

[0002] The World Health Organization defines volatile organic compounds (VOCs) as various organic compounds with a boiling point of 50 to 260°C at room temperature. Nanoporous carbon adsorbents are widely used in industrial VOCs waste gas control or recovery, indoor air purification, etc. due to their rich pore structure, low price and abundant sources. However, a single nanoporous carbon material has a single pore structure, and due to the high internal mass transfer resistance and the thermal activation reaction of VOCs, it is easy to form a large amount of high-boiling point carbonaceous products at the adsorption interface, thereby causing the adsorbent to be deactivated.

[0003] Studies have shown that transition metal modification can effectively inhibit the thermal activation reaction and dehydrogenation reaction process of VOCs on the adsorbent, thereby effectively reducing the formation of high-boiling point carbonaceous products during the desorption process, and theoretically improve the thermal desorption regeneration of the adsorbent.

[0004] However, most of the existing methods for modifying porous carbon with transition metals are post-modification methods, that is, surface modification of the synthesized porous carbon. The transition metals in the post-modification method may block the pore structure of the porous carbon, so that the regeneration performance of the porous carbon is not significantly improved. For example, a Chinese patent for a composite photocatalyst and its preparation method and application provides a post-modification method for porous carbon.

[0005] Therefore, new technologies are developed to solve the problems of the current post-modification methods of transition metal-modified porous carbon. Summary of the invention

[0006] The primary purpose of the present invention is to overcome the problem that the post-modification method of the above-mentioned existing transition metal-modified porous carbon does not significantly improve the regeneration performance of the porous carbon, and to provide a method for preparing a nano-metal-modified biomass carbon adsorbent. The preparation method of the present invention is a nano-metal in-situ modification method, and the pores of the obtained nano-metal-modified biomass carbon adsorbent will not be blocked by metal elements or metal oxides, and the network interweaving structure has high stability, so the nano-metal-modified biomass carbon adsorbent has a high adsorption capacity retention rate after multiple cycles of use, that is, good regeneration performance.

[0007] A further object of the present invention is to provide a nano-metal modified biomass carbon adsorbent prepared by the above preparation method.

[0008] Another object of the present invention is to provide an application of the above-mentioned nano-metal modified biomass carbon adsorbent in the adsorption of volatile organic compounds.

[0009] The above-mentioned object of the present invention is achieved by the following technical solutions:

[0010] A method for preparing a nano-metal modified biomass carbon adsorbent comprises the following steps:

[0011] S1. preparing a colloidal dispersion of a carbon source, a transition metal salt, cellulose and a solvent;

[0012] S2. hydrothermally carbonizing the colloidal dispersion to obtain a carbon composite;

[0013] S3. performing a first heat treatment and a second heat treatment on the carbon composite in an inert gas atmosphere, to obtain the nano-metal-modified biomass carbon adsorbent;

[0014] The carbon source in step S1 is at least one of monosaccharide or disaccharide;

[0015] In step S3, the temperature of the first heat treatment is 300-450°C, and the temperature of the second heat treatment is 550-950°C.

[0016] The present invention first prepares a colloidal dispersion liquid with a specific carbon source, a transition metal salt, cellulose and a solvent, wherein the colloidal state is conducive to the uniform dispersion, distribution and mutual contact of the carbon source and the transition metal salt; then performs a hydrothermal carbonization treatment, and the formed carbon composite is a composite of metal ions, metal oxides, spherical carbon and carbon fibers; then performs a first heat treatment and a second heat treatment on the carbon composite, wherein during the first heat treatment, the metal ions and part of the metal oxides in the carbon composite are reduced to metal elements, and a cross-linking system with spherical carbon and carbon fibers as the primary carbon skeleton and uniformly loaded with metal elements and metal oxides is formed; the primary carbon skeleton of the cross-linking system undergoes carbon skeleton reformation under the catalysis of the transition metal element during the second heat treatment, thereby obtaining a nano-metal modified biomass carbon adsorbent having multi-level pores, a stable network interwoven structure and loaded with transition metals.

[0017] The preparation method of the present invention is a nano-metal in-situ modification method, so the pores of the obtained nano-metal modified biomass carbon adsorbent will not be blocked by metal elements or metal oxides, and the network interweaving structure has high stability. Therefore, the nano-metal modified biomass carbon adsorbent has a high adsorption capacity retention rate after multiple cycles of use, that is, good regeneration performance.

[0018] In addition, the initial adsorption capacity of the nano-metal modified biomass carbon adsorbent obtained by the preparation method of the present invention is higher than that of the carbon adsorbent obtained by the post-modification method.

[0019] In addition, the preparation method of the present invention is simple and easy, which reduces the equipment cost; at the same time, the preparation process does not require the use of toxic and harmful organic solvents or secondary high-temperature activation and pore expansion, which reduces production costs and reduces harm to the environment.

[0020] Preferably, the transition metal salt is at least one of an iron salt, a cobalt salt, a nickel salt or a copper salt.

[0021] More preferably, the iron salt is at least one of ferric acetate, ferric sulfate, ferric nitrate or ferric ethylenediaminetetraacetate.

[0022] More preferably, the cobalt salt is at least one of cobalt acetate or cobalt nitrate.

[0023] More preferably, the nickel salt is at least one of nickel acetate or nickel nitrate.

[0024] More preferably, the copper salt is at least one of copper acetate or copper sulfate.

[0025] In the present invention, the cellulose in step S1 refers to cellulose that can form a gel when added to water.

[0026] Preferably, the cellulose is at least one of bacterial cellulose or plant cellulose.

[0027] Preferably, the monosaccharide is at least one of glucose or fructose.

[0028] Preferably, the disaccharide is sucrose.

[0029] Preferably, the solvent is a mixture of alcohol and water.

[0030] The use of a solvent containing alcohol is more conducive to the formation of spherical carbon from the carbon source during hydrothermal carbonization.

[0031] More preferably, the mass concentration of alcohol in the solvent is 1-50%, specifically 1%, 5%, 10%, 20%, 30%, 40% or 50%.

[0032] More preferably, the alcohol is at least one of methanol, ethanol, ethylene glycol or glycerol.

[0033] Preferably, the mass volume ratio of the carbon source to the solvent is 1 g: (1-70) mL, specifically 1 g: 1 mL, 1 g: 5 mL, 1 g: 10 mL, 1 g: 20 mL, 1 g: 40 mL, 1 g: 60 mL or 1 g: 70 mL.

[0034] Preferably, the mass volume ratio of the transition metal salt to the solvent is 1 g: (40-2500) mL, specifically 1 g: 40 mL, 1 g: 100 mL, 1 g: 200 mL, 1 g: 300 mL, 1 g: 400 mL 1 g: 500 mL, 1 g: 800 mL, 1 g: 1000 mL, 1 g: 1500 mL or 1 g: 2500 mL.

[0035] More preferably, the mass volume ratio of the transition metal salt to the solvent is 1g: (300-400)mL. When the mass volume ratio of the transition metal salt to the solvent is controlled within this range, the adsorption capacity retention rate of the nano-metal modified biomass carbon adsorbent is higher and the regeneration performance is better.

[0036] Preferably, the mass volume ratio of the cellulose to the solvent is 1 g: (10-1750) mL, specifically 1 g: 10 mL, 1 g: 100 mL, 1 g: 200 mL, 1 g: 500 mL, 1 g: 800 mL, 1 g: 1000 mL, 1 g: 1500 mL or 1 g: 1750 mL.

[0037] Preferably, the cellulose is mixed with a carbon source, a transition metal salt and a solvent in the form of a gel and then prepared into a colloidal dispersion.

[0038] More preferably, the volume ratio of the gel to the solvent is 1:(1-17.5), and can be specifically 1:1, 1:2, 1:5, 1:10, 1:15 or 1:17.5.

[0039] More preferably, the mass volume ratio of cellulose to water in the gel is 1 g: (10-500) mL, specifically 1 g: 10 mL, 1 g: 50 mL, 1 g: 100 mL, 1 g: 150 mL, 1 g: 200 mL, 1 g: 300 mL, 1 g: 400 mL or 1 g: 500 mL.

[0040] More preferably, the fiber diameter distribution of the cellulose is 10-100 nm.

[0041] More preferably, the purity of the cellulose is ≥90%.

[0042] Preferably, the process of preparing the colloidal dispersion in step S1 is: firstly mixing the carbon source, the transition metal salt and the solvent into a solution, and then adding the cellulose into the solution to obtain the colloidal dispersion.

[0043] Preferably, the hydrothermal carbonization time is 3 to 20 hours.

[0044] Preferably, the temperature of the hydrothermal carbonization is 130-200°C.

[0045] More preferably, the temperature is raised to the hydrothermal carbonization temperature at a rate of 1-20°C / min.

[0046] Preferably, after the hydrothermal carbonization in step S2, the steps of filtering, washing and drying are also included.

[0047] Preferably, the temperature is raised to the first heat treatment temperature at a rate of 1-10°C / min.

[0048] Preferably, the first heat treatment lasts for 1 to 5 hours.

[0049] Preferably, the temperature of the second heat treatment is increased at a rate of 1-10°C / min.

[0050] Preferably, the second heat treatment lasts for 1 to 5 hours.

[0051] Preferably, the temperature of the second heat treatment is 600-750° C. When the temperature of the second heat treatment is controlled within this range, the nano-metal modified biomass carbon adsorbent not only has good regeneration performance, but also has a higher initial adsorption capacity.

[0052] Preferably, the inert gas is at least one of argon, nitrogen or helium.

[0053] The present invention also protects a nano-metal modified biomass carbon adsorbent prepared by the above preparation method.

[0054] Preferably, in the nano-metal modified biomass carbon adsorbent, micropores account for 48-55% of the total pore volume, and mesopores account for 38-45% of the total pore volume.

[0055] The present invention also protects the use of the nano metal modified biomass carbon adsorbent in adsorbing volatile organic compounds.

[0056] Preferably, the volatile organic compound is at least one of benzene series, aldehydes, esters, ketones or halogenated hydrocarbons.

[0057] More preferably, the benzene series compound is toluene.

[0058] More preferably, the ester is ethyl acetate.

[0059] Compared with the prior art, the present invention has the following beneficial effects:

[0060] The preparation method of the present invention is a nanometal in-situ modification method. The pores of the obtained nanometal modified biomass carbon adsorbent will not be blocked by metal elements or metal oxides, and the network interweaving structure has high stability. Therefore, the nanometal modified biomass carbon adsorbent has a high adsorption capacity retention rate after multiple cycles of use, that is, good regeneration performance. In addition, the initial adsorption capacity of the nanometal modified biomass carbon adsorbent obtained by the preparation method of the present invention is higher than that of the carbon adsorbent obtained by the post-modification method. In addition, the preparation method of the present invention is simple and easy, which reduces the equipment cost; at the same time, the preparation process does not require the use of toxic and harmful organic solvents or secondary high-temperature activation to expand the pores, which reduces production costs and reduces harm to the environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0061] Figure 1This is the TEM image of the nano-metal modified porous carbon adsorbent prepared in Example 1.

[0062] Figure 2 The nitrogen adsorption-desorption isotherm diagram and pore size distribution diagram of the nano-metal modified porous carbon adsorbent prepared in Example 1 are shown.

[0063] Figure 3 This is the nitrogen adsorption-desorption isotherm diagram of the nano-metal modified porous carbon adsorbent prepared in Example 2. DETAILED DESCRIPTION

[0064] In order to more clearly and completely describe the technical solution of the present invention, the present invention is further described in detail through specific embodiments below. It should be understood that the specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention. Various changes can be made within the scope of the rights of the present invention.

[0065] Example 1

[0066] This embodiment provides a method for preparing a nano-metal modified biomass carbon adsorbent, comprising the following steps:

[0067] 1) 0.139 g of ferric acetate and 5 g of sucrose were added to a mixture of 50 mL of ethanol and water, and the mixture was stirred to form a solution, and then 20 mL of bacterial cellulose gel was added to the solution to obtain a colloidal dispersion. The preparation method of bacterial cellulose gel is as follows: bacterial cellulose (Beijing Guanlan Technology Co., Ltd.) and water were ultrasonically mixed at a mass volume ratio of 1 g: 100 mL for 30 minutes to obtain bacterial cellulose gel; the mass concentration of ethanol in the mixture was 14%.

[0068] 2) The colloidal dispersion was transferred to a 100 mL reactor, and then heated to 180° C. at a rate of 10° C. / min in an oven and kept warm for 6 h. The obtained chocolate brown carbon composite was filtered, washed once with ethanol centrifugation, and then washed with distilled water until neutral and then dried.

[0069] 3) placing the carbon composite dried in step 2) in a tubular furnace, and performing a first heat treatment and a second heat treatment in an argon atmosphere, wherein the first heat treatment condition is: heating to 400°C at 5°C / min and keeping warm for 4 hours, and the second heat treatment condition is: heating from 400°C to 600°C at 5°C / min and keeping warm for 2 hours, thereby obtaining a nano-metal modified biomass carbon adsorbent.

[0070] Example 2

[0071] This embodiment provides a method for preparing a nano-metal modified biomass carbon adsorbent. The difference from Embodiment 1 is that the second heat treatment condition in step 3) is: heating from 400° C. to 750° C. at 5° C. / min and keeping the temperature for 2 h.

[0072] Example 3

[0073] This embodiment provides a method for preparing a nano-metal modified biomass carbon adsorbent. The difference from Embodiment 1 is that the second heat treatment condition in step 3) is: heating from 400° C. to 850° C. at 5° C. / min and keeping the temperature for 2 h.

[0074] Example 4

[0075] This embodiment provides a method for preparing a nano-metal modified biomass carbon adsorbent. The difference from Embodiment 1 is that the second heat treatment condition in step 3) is: heating from 400° C. to 950° C. at 5° C. / min and keeping the temperature for 2 h.

[0076] Example 5

[0077] This embodiment provides a method for preparing a nano-metal modified biomass carbon adsorbent, which is different from that of Embodiment 1 in that in step 1), the amount of ferric acetate used is 1.112 g.

[0078] Example 6

[0079] This embodiment provides a method for preparing a nano-metal modified biomass carbon adsorbent, comprising the following steps:

[0080] 1) 0.139 g of ferric acetate and 1.5 g of sucrose are added to a mixture of 50 mL of ethanol and water, and the mixture is stirred to form a solution, and then 30 mL of bacterial cellulose gel is added to the solution to obtain a colloidal dispersion. The preparation method of the bacterial cellulose gel is as follows: the bacterial cellulose and water are ultrasonically mixed at a volume ratio of 1 g: 100 mL for 30 minutes to obtain the bacterial cellulose gel; the mass concentration of ethanol in the mixture is 14%.

[0081] 2) The colloidal dispersion was transferred to a 100 mL reactor, and then heated to 200° C. at a rate of 10° C. / min in an oven and kept warm for 6 h. The obtained chocolate brown carbon composite was filtered, washed once with ethanol centrifugation, and then washed with distilled water until neutral and then dried.

[0082] 3) placing the carbon composite dried in step 2) in a tubular furnace, and performing a first heat treatment and a second heat treatment in sequence under an argon atmosphere, wherein the first heat treatment condition is: heating to 350°C at 5°C / min and keeping warm for 4 hours, and the second heat treatment condition is: heating from 400°C to 600°C at 5°C / min and keeping warm for 2 hours, thereby obtaining a nano-metal modified biomass carbon adsorbent.

[0083] Comparative Example 1

[0084] This comparative example provides a method for preparing a biomass carbon adsorbent, which is different from Example 1 in that the second heat treatment condition in step 3) is: heating from 400°C to 420°C at 5°C / min and keeping the temperature for 2h.

[0085] Comparative Example 2

[0086] This comparative example provides a method for preparing a biomass carbon adsorbent. The difference from Example 1 is that the first heat treatment is not performed in step 3).

[0087] Comparative Example 3

[0088] This comparative example provides a method for preparing a biomass carbon adsorbent. Different from Example 1, the second heat treatment is not performed in step 3).

[0089] Comparative Example 4

[0090] This comparative example provides a method for preparing a biomass carbon adsorbent, comprising the following steps:

[0091] 1) 5 g of sucrose was added to a mixture of 50 mL of ethanol and water, and the mixture was stirred to form a solution. Then 20 mL of bacterial cellulose gel was added to the solution to obtain a colloidal dispersion. The mass concentration of ethanol in the mixture was 14%.

[0092] 2) The colloidal dispersion was transferred to a 100 mL reactor, and then heated to 180 ° C in an oven at a rate of 10 ° C / min, and kept warm for 6 hours to obtain a chocolate brown carbon composite, which was filtered, washed once with ethanol shaking centrifugation, and then washed with distilled water until neutral and dried; 0.139 g of ferric acetate and the carbon composite were redispersed in 70 mL of water, stirred for 6 hours, centrifuged and dried to obtain a biomass carbon adsorbent precursor.

[0093] 3) The biomass carbon adsorbent precursor of step 2) is placed in a tubular furnace, and the first heat treatment and the second heat treatment are performed in sequence under an argon atmosphere. The first heat treatment condition is: heating to 400°C at 5°C / min and keeping warm for 4 hours, and the second heat treatment condition is: heating from 400°C to 600°C at 5°C / min and keeping warm for 2 hours to obtain a biomass carbon adsorbent.

[0094] Comparative Example 5

[0095] This comparative example provides a method for preparing a biomass carbon adsorbent, which is different from Example 1 in that no sucrose is added in step 1).

[0096] Sample characterization and performance testing

[0097] 1. Transmission Electron Microscopy Characterization

[0098] The nano-metal modified biomass carbon adsorbent prepared in Example 1 was placed in an ethanol system for ultrasonic dispersion treatment for 30 minutes, and then the sample after ultrasonic dispersion treatment was observed using a transmission electron microscope. The results are as follows: Figure 1 As shown. Figure 1 It can be seen that after 30 minutes of ultrasonic dispersion treatment, the nano-iron is tightly coupled with the porous carbon and forms a dense composite structure. The nano-metal modified biomass carbon adsorbent can maintain a stable network interweaving structure, which indicates that the prepared nano-metal modified biomass carbon adsorbent has a stable adsorption and capture efficiency. The transmission electron micrographs of other embodiments are similar to those of Example 1, indicating that the nano-metal modified biomass carbon adsorbent prepared by the present invention has a stable adsorption and capture efficiency.

[0099] 2. Nitrogen isothermal adsorption and desorption test

[0100] The nano-metal modified biomass carbon adsorbents prepared in Example 1 and Example 2 were subjected to nitrogen isothermal adsorption and desorption tests. The test results are as follows: Figure 2 and Figure 3 shown.

[0101] from Figure 2 and Figure 3 It can be seen that the isothermal adsorption-desorption curve shows an obvious hysteresis loop, indicating that the nano-metal modified biomass carbon adsorbent of the present invention has a high adsorption capacity.

[0102] Further from Figure 2 It can be seen from the BET pore size distribution diagram in that the nano-metal modified biomass carbon adsorbent in Example 1 is mainly composed of micropores and mesopores, which account for approximately 50% and 40% of the total pore volume, respectively. This indicates that the prepared nano-metal modified biomass carbon adsorbent can form an effective multi-level pore structure, which is beneficial to the adsorption of volatile organic compounds.

[0103] The results of nitrogen isothermal adsorption-desorption tests of other examples are similar to those of Example 1.

[0104] 3. Adsorption-desorption test |

[0105] The nano-metal modified biomass carbon adsorbent prepared in each example and the biomass carbon adsorbent prepared in each comparative example were used to perform adsorption-desorption cycle tests on ethyl acetate and toluene. The test results are shown in Table 1.

[0106] Table 1 Initial adsorption capacity and adsorption capacity retention after 5 cycles

[0107]

[0108]

[0109] As can be seen from Table 1, the nano-metal modified biomass carbon adsorbents prepared in Examples 1 to 5 have an adsorption capacity retention rate of ethyl acetate of more than 93% after 5 cycles; and an adsorption capacity retention rate of toluene of more than 98% after 5 cycles, which indicates that the nano-metal modified biomass carbon adsorbent prepared in the present invention has a high adsorption capacity retention rate for ethyl acetate and toluene. The test results of Example 6 are similar to those of Example 1.

[0110] In addition, the initial adsorption capacity of the nano-metal modified biomass carbon adsorbents prepared in Examples 1 to 5 for ethyl acetate is above 78 mg / g, and the initial adsorption capacity for toluene is above 106 mg / g. Among them, when the temperature of the second heat treatment is increased from 600°C to 950°C, the initial adsorption capacity of the nano-metal modified biomass carbon adsorbent for toluene first increases and then decreases; the initial adsorption capacity of the nano-metal modified biomass carbon adsorbent for ethyl acetate gradually decreases, and after 850°C, the initial adsorption capacity fluctuates in a certain range (78-85 mg / g). The reason for the fluctuation of the initial adsorption capacity in a certain range (78-85 mg / g) is that higher temperatures will cause part of the pore structure to collapse, reducing the adsorption effect of the pore structure; but at the same time, more Fe sites are exposed, and the Fe sites have a strong coordination effect with ethyl acetate. The two effects cause the initial adsorption capacity of ethyl acetate to fluctuate.

[0111] The biomass carbon adsorbents of Comparative Examples 1 and 3 have low adsorption capacity retention rates for ethyl acetate and toluene, because the temperature of the second heat treatment is too low or the second heat treatment is not performed, and the carbon skeleton cannot be reformed to form a stable network interweaving structure. In addition, the initial adsorption amount of ethyl acetate and toluene by the biomass carbon adsorbents of Comparative Examples 1 and 3 is also low, because the carbon skeleton cannot be reformed to form more pore structures.

[0112] The biomass carbon adsorbent of Comparative Example 2 has a low adsorption capacity retention rate for ethyl acetate and toluene because the second heat treatment is directly performed without the first heat treatment in step 3), resulting in agglomeration of the transition metal-containing components, making it difficult to effectively catalyze carbon skeleton reforming.

[0113] Comparative Example 4 is a post-modification method, and the biomass carbon adsorbent prepared therefrom has a low adsorption capacity retention rate for ethyl acetate and toluene; the initial adsorption capacity is not as good as that of Example 1.

[0114] The biomass carbon adsorbent of Comparative Example 5 has a low adsorption capacity retention rate for ethyl acetate and toluene because spherical carbon cannot be formed without the addition of sucrose, and the lack of cross-linking nodes makes it impossible to form a stable network interwoven structure.

[0115] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A method for preparing a nano-metal modified biomass carbon adsorbent, characterized in that: The following steps are involved: S1. preparing a colloidal dispersion of a carbon source, a transition metal salt, cellulose and a solvent; S2. hydrothermally carbonizing the colloidal dispersion to obtain a carbon composite; S3. performing a first heat treatment and a second heat treatment on the carbon composite in an inert gas atmosphere, to obtain the nano-metal-modified biomass carbon adsorbent; The carbon source in step S1 is at least one of monosaccharide or disaccharide; In step S3, the temperature of the first heat treatment is 300-450°C, and the temperature of the second heat treatment is 550-950°C.

2. The preparation method according to claim 1, characterized in that: The transition metal salt is at least one of an iron salt, a cobalt salt, a nickel salt or a copper salt.

3. The preparation method according to claim 1, characterized in that: The cellulose is at least one of bacterial cellulose and plant cellulose.

4. The preparation method according to claim 1, characterized in that: The temperature of the hydrothermal carbonization is 130-200°C.

5. The preparation method according to claim 1, characterized in that: The solvent is a mixture of alcohol and water.

6. The preparation method according to claim 1, characterized in that: The mass volume ratio of the carbon source to the solvent is 1 g: (1-70) mL.

7. The preparation method according to claim 1, characterized in that: The mass volume ratio of the cellulose to the solvent is 1 g: (10-1750) mL.

8. The preparation method according to claim 1, characterized in that: The mass volume ratio of the transition metal salt to the solvent is 1 g: (40-2500) mL.

9. A nano-metal modified biomass carbon adsorbent, characterized in that: It is prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the nano-metal modified biomass carbon adsorbent according to claim 9 in adsorbing volatile organic compounds.